The Role of Educational Training Programs in Developing Teachers’ Teaching Skills from their Own Standpoint "A Field Study at the Basic Education First-Cycle Schools in the City of Lattakia" - Yousef, Asef; Zumorrod, Amira; Al-Hussein, Fadia Hussein (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The current research aimed to identify the first-cycle teachers’ standpoint regarding the extent of advantage that they have taken of training programs in terms of developing their teaching skills: lesson preparation and planning skill, lesson implementation skill, and lesson evaluation skill. It also aimed to figure out the obstacles that limit this advantage, seeking to provide some suggestions to face such obstacles. The method adopted was the descriptive one, and the tool was a questionnaire, prepared by the researcher, reviewed by specialists and studied in terms of its psychometric characteristics. The research was applied on a sample of 202 male and female teachers at the first-cycle schools in the city of Lattakia. The research concluded that the extent of contribution of the training programs regarding the development of the teachers’ teaching skills from their own standpoint was at a high degree; it was high on both lesson preparation and planning skill and lesson evaluation skill, while it was moderate for lesson implementation skill. Moreover, the results showed a difference in the standpoint of teachers about the extent of the advantage that they have taken of training programs according to the variable of the academic qualification (on the behalf of those who have Educational Habilitation Diploma), according to the variable of experience years (on the behalf of those who have more than 10 years of experience), and according to the variable of the number of training courses (on the behalf of teachers who have undergone more than three courses). هدفت البحث الحالي إلى تعرّف وجهة نظر معلمي الحلقة الأولى حول درجة إفادتهم من البرامج التدريبية في تطوير مهاراتهم التدريسية (مهارة الإعداد والتخطيط للدرس، ومهارة تنفيذ الدرس، ومهارة تقويم الدرس), كما هدف إلى تعرّف المعوقات التي تحد من هذه الفائدة, وسعى لتقديم مقترحات لمواجهة هذه المعوقات. كان المنهج وصفي والأداة استبانة (معدّة من قبل الباحثة ومحكمة من قبل اختصاصيين والخصائص السيكومترية مدروسة), حيث طبقت على عينة مؤلفة من (202) معلماً ومعلمةً في مدارس الحقلة الأولى في مدينة اللاذقية. أظهرت نتائج البحث أن درجة مساهمة البرامج التدريبية في تطوير مهارات المعلمين التدريسية من وجهة نظرهم جاءت بدرجة مرتفعة (حيث كانت مرتفعة على مهارتي: الإعداد والتخطيط للدرس ومهارة تقويم الدرس، ومتوسطة على مهارة تنفيذ الدرس)، وبينت النتائج وجود اختلافُ في وجهات نظر المعلمين حول درجة إفادتهم من البرامج التدريبية بحسب متغير المؤهل العلمي (لصالح حملة دبلوم التأهيل التربوي), وبحسب متغير سنوات الخبرة (لصالح من لديهم خبرة أكثر من 10 سنوات), وبحسب متغير عدد الدورات التدريبية (لصالح المعلمين الذين خضعوا لأكثر من 3 دورات).